Utility of salivary biomarkers for diagnosis and monitoring the prognosis of nicotine addiction - A systematic review - S. Shreya; Manoj Annamalai; Vasanti Lagali Jirge; Sneha Sethi (Journal of Oral Biology and Craniofacial Research)
Objectives: Tobacco and smoke associated with tobacco comprises of a mixture of more than 9500 chemical compounds, most of which have been identified as harmful. Two of the most potent carcinogens found in cigarette smoke are N′-nitrosonornicotine (NNN) and polycyclic aromatic hydrocarbons (PAHs). The most commonly used method to detect and monitor nicotine addiction is via serum cotinine levels. Though considered the gold standard, there is a decline in preventive screening and diagnostic testing due to the fear of pain from invasive testing. Data sources and study selection: A structured literature search was performed using the search engines PubMed and Google scholar following the PRISMA guidelines for systematic reviews. The titles and abstracts were retrieved and analysed, followed by full-text relevant data extraction in addition to a risk-of-bias analysis. Data extraction and synthesis: A total of 37 studies were included in the systematic review. Salivary cotinine levels were compared between smokers and non-smokers, cigarette smokers and water pipe smokers, water pipe smokers and non-smokers. Lactate dehydrogenase salivary levels were compared between smokers and non-smokers, and salivary thiocyanate were compared between smokers and non-smokers. Conclusions: Identifying biomarkers with high performance in terms of sensitivity and specificity will contribute to accelerating future research in this domain.